On mesoscale modeling of concrete: Role of heterogeneities on local stresses, strains, and representative volume element. (January 2023) - Thakur, Mohmad M.; Henningsson, N. Axel; Engqvist, Jonas; Autran, Pierre-Olivier; Wright, Jonathan P.; Hurley, Ryan C.
Abstract: The mechanics of concrete can be understood comprehensively only if its heterogeneous microstructure is considered in experiments and simulations. We combine mesoscale modeling, in-situ X-ray computed tomography imaging, and in-situ 3D X-ray diffraction measurements for one of the first times to investigate the role of heterogeneities on macroscopic and microscopic responses in concrete. The focus here is on heterogeneities at the micron scale: aggregates, cement paste, interfacial transition zone, high-density phases, and voids. We specifically seek to answer whether all levels of heterogeneities are essential in predicting: (a) elastic macroscopic stress–strain response, (b) microscopic elastic stress–strain concentrations, and (c) representative volume element size for elastic responses. The results demonstrate the significant influence of heterogeneities on local strains in matrix phases and the minimal influence of heterogenities on stresses in individual grains.